Regulation of agrin-induced acetylcholine receptor aggregation by Ca++ and phorbol ester (The Rockefeller University Press, 1988)
Agrin, a protein extracted from the electric organ of Torpedo californica, induces the formation of specializations on cultured chick myotubes that resemble the postsynaptic apparatus at the neuromuscular junction. The aim of the studies reported here was to characterize the effects of agrin on the distribution of acetylcholine receptors (AChRs) and cholinesterase as a step toward determining agrin's mechanism of action. When agrin was added to the medium bathing chick myotubes small (less than 4 micron 2) aggregates of AChRs began to appear within 2 h and increased rapidly in number until 4 h. Over the next 12-20 h the number of aggregates per myotube decreased as the mean size of each aggregate increased to approximately 15 micron 2. The accumulation of AChRs into agrin-induced aggregates occurred primarily by lateral migration of AChRs already in the myotube plasma membrane at the time agrin was added to the cultures. Aggregates of AChRs and cholinesterase remained as long as agrin was present in the medium; if agrin was removed the number of aggregates declined slowly. The formation and maintenance of agrin-induced AChR aggregates required Ca++, Co++ and Mn++ inhibited agrin-induced AChR aggregation and increased the rate of aggregate dispersal. Mg++ and Sr++ could not substitute for Ca++. Agrin- induced receptor aggregation also was inhibited by phorbol 12-myristate 13-acetate, an activator of protein kinase C, and by inhibitors of energy metabolism. The similarities between agrin's effects on cultured myotubes and events that occur during formation of neuromuscular junctions support the hypothesis that axon terminals release molecules similar to agrin that induce the differentiation of the postsynaptic apparatus.